2021
DOI: 10.1002/hep4.1585
|View full text |Cite
|
Sign up to set email alerts
|

Liver Chemistries in Patients With COVID-19 Who Were Discharged Alive or Died: A Meta-analysis

Abstract: Although abnormal liver chemistries are linked to a higher risk of coronavirus disease 2019 (COVID-19)-related death, liver manifestations may be diverse and even confusing. Thus, we performed a meta-analysis of published liver manifestations and described the liver damage in patients with COVID-19 who died or discharged alive. We searched PubMed, Google Scholar, medRxiv, bioRxiv, the Cochrane Library, Embase, and three Chinese electronic databases through April 22, 2020. We analyzed pooled data on liver chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Similar to our study, most other studies reveal a predominant pattern of disturbances in liver enzymes in COVID-19 patients, specifically higher AST elevation than ALT elevation[ 17 - 19 ]. A meta-analysis by Wu et al [ 20 ] found that low serum albumin and high GGT were the most frequent abnormalities on admission and that ALT elevation occurred most frequently during hospitalization, which they speculate may be due to the inclusion of patients with pre-existing liver disease.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our study, most other studies reveal a predominant pattern of disturbances in liver enzymes in COVID-19 patients, specifically higher AST elevation than ALT elevation[ 17 - 19 ]. A meta-analysis by Wu et al [ 20 ] found that low serum albumin and high GGT were the most frequent abnormalities on admission and that ALT elevation occurred most frequently during hospitalization, which they speculate may be due to the inclusion of patients with pre-existing liver disease.…”
Section: Discussionsupporting
confidence: 91%
“…COVID-19 patients with gastrointestinal symptoms may have an increased risk of liver injury (OR=2•71, 95% CI: 1•52–4•83) [63] . Liver injury diagnosis mainly depends on biochemical indicators including alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBIL), alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT), albumin (ALB), and prothrombin time (PT) [64] .…”
Section: Covid-19 and The Livermentioning
confidence: 99%
“…P-value analyses were two-sided and a p-value of less than 0.05 was considered statistically significant. The Positive Predictive Values (PPV) and the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified a close correlation between hypoalbuminemia and mortality in CAP patients, whereas little is known as for SARS-CoV-2 pneumonia [21][22][23][24][25][26][27]. In fact, it has been recently demonstrated that an albumin level <3.5 g/dL was associated with worse outcome and coagulopathy [26][27].…”
Section: Prediction Of Intra-hospital Mortalitymentioning
confidence: 99%